(untitled) (Vallis Aurea, 2018)
This paper analyses the relationship between the teacher technology competence and their use of technology under the mediating influence of ease of use. The paper presents a set of results that are empirically tested on a sample of 387 high school and higher secondary school teachers from across 14 districts in Kerala, a southern state in India. A majority of these respondents had a teaching experience of more than eleven years and had been using computers for more than five years. The results reveal that technology competence among these teachers was moderately but positively correlated to their actual use of technology andthis relationship was found to be mediated by ease of use of technology. The paper discusses the implications of these findings and makes recommendations to leverage these relationships so as to achieve greater technology integration.